2010
DOI: 10.1242/jeb.041277
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutritional condition on spring migration: do migrants use resource availability to keep pace with a changing world?

Abstract: SUMMARYBecause of their reliance on temporally predictable resources across large spatial scales, migratory birds may be especially vulnerable to anthropogenic climate and land-use changes. Although some long-distance migrants appear unable to adjust to phenological shifts on their wintering grounds, several short-and medium-distance migrants appear to have altered the timing and/or distance of their yearly movements to compensate for the environmental effects of global warming. Which environmental cues are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…A recent experimental study demonstrated that migration phenology in juncos is dependent on food availability and its effects on condition (Bridge et al, 2010). Males of other songbird species, such as the American redstart (Setophaga ruticilla), that winter in higher quality winter habitats arrive early at breeding sites and ultimately produce more offspring Reudink et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent experimental study demonstrated that migration phenology in juncos is dependent on food availability and its effects on condition (Bridge et al, 2010). Males of other songbird species, such as the American redstart (Setophaga ruticilla), that winter in higher quality winter habitats arrive early at breeding sites and ultimately produce more offspring Reudink et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Marra and Holberton, 1998;Marra and Holmes, 2001;Latta and Faaborg, 2002;Brown and Sherry, 2006;Studds and Marra, 2007;Smith et al, 2010) and the timing of migration Studds and Marra, 2005;Gunnarsson et al, 2006;Bridge et al, 2010). This can ultimately lead to carry-over effects on breeding success Reudink et al, 2009;Inger et al, 2010), survival (Johnson et al, 2006;Angelier et al, 2009) and natal dispersal (Studds et al, 2008), such that non-breeding and breeding life history stages interact across geographical space.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the annual variation in mean passage time in the Mediterranean area was positively correlated with primary production in both departure region and passage areas in several trans-Sahara migrants [10]. Similarly, favourable environmental conditions in non-breeding areas have resulted in late arrival at the breeding sites and good environmental conditions during stopover in early arrival at the breeding sites [15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, high spring hunting pressure (e.g., Light Goose Conservation Order) may also influence regional movements (Béchet et al 2003). Besides, interannual deviations in precipitation δ 2 H patterns (Brewster 2009) can alter δ 2 H isotopic spatial patterns in vegetation and may thus limit the precision of the assignment approach (Wunder and Norris 2008, but see Hobson 2011); the spatial distributions of δ 13 C and δ 15 N values in food webs are likely less prone to unpredictable betweenyear variations (Bukata and Kyser 2007). We did not detect marked variations in δ 2 H, δ 13 C, and δ 15 N patterns in LA and TX Coast samples between years; yet, interannual deviance can vary spatially and may require year-specific correction algorithms for assignment ).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution and abundance of Snow Geese in the RWB is influenced by natural and anthropogenically caused variations in water conditions, hunting pressure Sullivan 2009, Webb et al 2010), and migration chronology, which in many species is related to spring environmental variables, e.g., climatic conditions, food availability (Jonzén et al 2006, Bridge et al 2010, Studds and Marra 2011. Additional sampling of birds in the western RWB wetlands is needed to assess spatial distribution of geese in the RWB according to their wintering areas; heterogeneous spatial distribution in the RWB of waterfowl from diverse wintering areas was previously reported (Pearse et al 2011).…”
Section: Discussionmentioning
confidence: 99%